Microeconomic policies in the new economy - Rune Stenbacka (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
The core industries of the new information economy are characterized by imperfect competition, asymmetric information or external effects. Thus, well-designed microeconomic policies, in the form of competition policies, technology policies or combinations of these, have strong potential of generating welfare improvements and promoting social efficiency. This paper emphasizes innovation-intensive competition, strong technological scale economies, network effects and complementarity between system components as characteristic features of the core industries in the information economy. With reference to these features the study explores the implications for microeconomic policies from the point of view of competition analysis. The combination of strong technological scale economies on the supply side and network effects on the demand side makes market structures with high concentration and dominant firms both likely and efficient. On the other hand, a firm possessing a dominant market position and operating in a network industry has access to a more efficient set of instruments in order to abuse its dominant market position relative to a firm operating in a traditional industry. This study argues that the recognition of these two counteracting aspects forms a necessary condition for the design of successful microeconomic policies in contemporary high-tech markets. It is also emphasized that efficient competition policy in these markets has to face an inherent structural trade-off between the exploitation of strong scale economies and the promotion of entry and small enterprises.
Keywords: L40; L50; O3; 330; competition policy; technology policy; network industries; Datenverarbeitungswirtschaft; Wettbewerbspolitik; Forschungs- und Technologiepolitik; Welt; New Economy